2021
DOI: 10.1021/acs.iecr.1c03687
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Particle Suspensions in a Liquid–Solid Stirred Tank with Baffles

Abstract: Stirred vessels have been widely used in the chemical and process industries, while particle suspensions in a liquid−solid stirred tank with baffles have little been studied. In this work, a particle suspension in a standard stirred tank driven by a Rushton turbine was simulated using large eddy simulation coupled with the Lagrangian particle tracking technique. The rotation speed was N = 313 rpm, and three particle sizes ranging from 200 to 2500 μm (St = 0.24−37.3) were considered. The simulation results incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…10 Turbulence and vortices are important characteristics of fluid flow. Using the large eddy simulation method, Wang et al 11 discussed the flow state in a liquid−solid stirred tank with baffles. They found that the strong turbulence and vortex generated by the impeller rotation promoted the mixing of particles and the double trailing vortices appeared behind the impeller blades.…”
Section: Introductionmentioning
confidence: 99%
“…10 Turbulence and vortices are important characteristics of fluid flow. Using the large eddy simulation method, Wang et al 11 discussed the flow state in a liquid−solid stirred tank with baffles. They found that the strong turbulence and vortex generated by the impeller rotation promoted the mixing of particles and the double trailing vortices appeared behind the impeller blades.…”
Section: Introductionmentioning
confidence: 99%